India against itself ;Assam and the politics of nationality - "Baruah, Sanjib" (Oxford, 1999)
In an era of failing states and ethnic conflict, violent challenges from dissenting groups in the former Yugoslavia, the former Soviet Union, several African countries, and India give cause for grave concern in much of the world. And it is in India where some of the most turbulent of these clashes have been taking place. One resulted in the creation of Pakistan, and militant separatist movements flourish in Kashmir, Punjab, Manipur, Mizoram, Nagaland, and Assam. In India Against Itself, Sanjib Baruah focuses on the insurgency in Assam in order to explore the politics of subnationalism.Baruah offers a bold and lucid interpretation of the political and economic history of Assam from the time it became a part of British India and a leading tea-producing region in the nineteenth century. He traces the history of tensions between pan-Indianism and Assamese subnationalism since the early days of Indian nationalism. The region's insurgencies, human rights abuses by gover
Keywords: Assam-Politics and government